Effects of alternate phases of fish oil and vegetable oil-based diets in Murray cod - David Francis; Giovanni Turchini; B Smith; S Ryan; S De Silva (2009)
Fish oil (FO)- and canola oil (CO)-based diets were regularly alternated in a daily cycle (amCO: alternation of CO in the morning and FO in the afternoon, and pmCO: alternation of FO in the morning and CO in the afternoon) or in a series of weekly cycles (2W: alternation of 2 weeks on CO and 2 weeks on FO, 4W: alternation of 4 weeks on CO and 4 weeks on FO), over a 16-week period in juvenile Murray cod ( Maccullochella peelii peelii ). No significant differences were observed between any of the treatments in relation to the final weight. However, fish subjected to the 2W schedule were larger ( P >0.05) than all other treatments (37.2 ± 0.30 vs. 34.3 ± 0.58 in the control treatment). Fish receiving the 2W treatment had a significantly lower total net disappearance of eicosapentaenoic acid 20:5n-3 (EPA) and docosahexaenoic acid 22:6n-3 (62.1% and 24.0% respectively) compared with the control treatment (fish continuously fed a blend of 50% FO and 50% CO). Likewise, Murray cod receiving the amCO daily schedule had a significantly lower total net disappearance of EPA in comparison with the CD and pmCO treatments. These data point towards the existence of cyclical mechanisms relative to fatty acid utilization/retention.